Účinky nových antineoplastických látek (Dimethoxybenfluronu and Oracinu) na kardiovaskulární systém - Macháčková, Jarmila; Geršl, Vladimír; Adamcová, Michaela; Mazurová, Yvona; Hrdina, Radomír; Mělka, Milan; Nobilis, Milan (Acta medica. Supplementum, 2000)
Anthracycline derivatives belong among the most effective antineoplastic drugs but their therapeutic use is limited by their side effects--a dose-related cardiotoxicity. The influence of repeated i.v. administration (once weekly, max. 10 weeks) of new antineoplastic agents--dimethoxybenfluron (DMB) (3,9-dimethoxybenfluron hydrochloride, C23H24O4NCl, M.w. 413.9, Institute of Experimental Biopharmaceutics, Czech Academy of Sciences, Hradec Králové, Czech Republic; 12 or 24 mg base/kg) and Oracin (6-[2-(2-hydroxyethyl)aminoethyl]-5,11-dioxo-5,6-dihydro-11H- indeno[1,2c]isoquinoline hydrochloride), C20H19N2O3Cl, M.w. 370.84, Research Institute for Pharmacy and Biochemistry, Prague, Czech Republic; 5 or 10 mg/kg) on cardiovascular, biochemical, haematological and histological parameters were studied in rabbits in vivo. Data obtained in these groups were compared with the group with experimentally induced cardiomyopathy (daunorubicin 50 mg/m2 i.v.) and with the control group (saline 1 ml/kg). Only mild and mostly no significant changes of the cardiovascular parameters (DMB 12 group: PEP:LVET ratio--0.408-0.502, LV dP/dtmax.--1337.0 kPa/s; DMB 24 group: PEP:LVET ratio--0.407-0.433, LV dP/dtmax.--1438.2 kPa/s), biochemical parameters (decrease in natrium, ALP and increase in glucose, GPX and GSH levels) and haematological parameters (increase in erythrocytes and decrease in leukocytes after the larger dose of the drug) were found in the dimethoxybenfluron groups. Repeated administration of the lower dose of Oracin induced only mild and mostly no significant changes of parameters (PEP:LVET ratio--0.393-0.475, LV dP/dtmax.--1092.4 kPa/s) in comparison with the control group. Though significant in some intervals, only a mild oscillation of the PEP:LVET ratio (0.368-0.446), decrease in LV dP/dtmax. (991.2 kPa/s) and--in comparison with control group--significantly higher blood pressure and lower heart rate were found after the higher dose of Oracin. In the most of haematological and biochemical parameters (with the exception of chlorides, protein and albumin levels) no significant changes were present. Histological examination of the heart revealed normal structure of the myocardium including minute changes of myocardium following administration of antineoplastic agents in all groups. Administration of new antineoplastic agents induced mostly mild changes of the followed-up parameters (PEP:LVET ratio, LV dP/dtmax., heart rate, levels of cardiac troponin T, survival of animals, haematological and biochemical parameters); the values of parameters were mostly significantly different from those in rabbits with daunorubicin-induced cardiomyopathy. On the basis of our results it is possible to conclude that the administration of dimethoxybenflurone and Oracin did not induce signs of cardiotoxicity in rabbits in vivo. This observation is considered to be important from the viewpoint of possible further clinical use of these new antineoplastic agents.
Keywords: Isoquinolines; Animals; Heart; Rabbits; Hemodynamics; daunomycin; hemodynamika; srdce; funkce levé komory srdeční; Antineoplastic Agents; protinádorové látky; Fluorenes; krevní tlak; isochinoliny; srdeční frekvence; Male; ethanolaminy; fluoreny; Daunorubicin; Ethanolamines; králíci; zvířata; mužské pohlaví; Blood Pressure; Myocardium; myokard; Heart Rate; Ventricular Function, Left